Challenges, success factors and strategies for women’s career development in the Australian construction industry (Construction Economics and Building, 2017)
Construction is traditionally a male industry. Women have long had difficulties entering or advancing their career in construction. Evidence shows that a diversified workforce with gender balance will bring about higher levels of productivity. Despite the importance of this issue, there have been limited studies on women’s career development in construction. This study aims to investigate women’s career development in the Australian construction industry, with objectives to evaluate the challenges and success factors of women’s career development in the construction industry and provide strategies for narrowing the gender imbalance. A mixed approach of questionnaire survey and interview were conducted with female practitioners in the construction industry. Forty-three completed questionnaires were received and 10 interviews were conducted. Stress, family-work balance, and negative perception towards women in construction were the top three challenges identified. Dedication, determination, and independence were the top three success factors of women in construction. This study recommends construction employers consider providing personal development programs and flexible working arrangement for their female employees. Significance of this study lies on contributing to understanding women’s career development in construction. Findings will be useful for government and professional institutions to promulgate strategies for advancing women’s career development in construction.